Dinamika Variasi Bahasa dalam Kerangka Sosiolinguistik terhadap Analisis Faktor-faktor Sosial dalam Perubahan Bahasa di Masyarakat Multibahasa pada Era Globalisasi - Azra Batrisyia; Mutiara Putri Nabila; Natalia Debriyanti Siringoringo; Safinatul Hasanah Harahap (Departement of Mathematics Education, 2024)
The problem raised in this research is how socioguistic language variations influence language changes in society in the current era of globalization. In this research, the researcher used a qualitative descriptive research method using a sociolinguistic approach. The research subject is a 58 year old trader who is a multilingual community and a Toba Batak speaker to gain in-depth views and understanding of language use in the social context of their community. Research data was obtained through participant observation, interviews, and documentation studies. Observations are carried out in real situations in multilingual communities to observe language use and existing language variations. Data is also collected from written sources. The results of this research show that the influence of globalization has brought about significant changes in everyday language use, where Toba Batak language tends to be replaced by Indonesian or English, especially among the younger generation. The aim of this research is to understand the impact of language change on multilingual societies in the era of globalization.